Compliance Analysis of Perum Peruri as an Electronic Certification Provider in Implementing Business Practices Management Webtrust Certification Authorities - Mahattu Jalinka; Wing Wahyu Winarno; Asro Nasiri (Journal of Computer Networks, Architecture and High Performance Computing, 2023)
Peruri is a trusted agency that collaborates with the Directorate General of Civil Registration and Population Administration (Ditjen Dukcapil) of the Ministry of Home Affairs of the Republic of Indonesia. It issues electronic certificates and electronic signatures using facial recognition authentication and compares live videos with Indonesian population data. This task demonstrates that Peruri is a trusted company in the field of digital security. In order to be recognized and maintain the credibility of the Certificate Policy (CP) and Certification Practice Statement (CPS) from Certification Authorities (CA) in the international community, Peruri needs to comply with various applicable standards. One of the international standards used is Webtrust for Certification Authorities. This study aims to analyze the capability level of Perum Peruri as an electronic certification provider in implementing Business Practices Management Webtrust Certification Authorities. The data used in this study consists of Perum Peruri's Certificate Policy (CP) and Certification Practice Statement (CPS). The analysis is conducted on the implementation of Business Practices Management Webtrust Certification Authorities based on the data of Perum Peruri's CP and CPS. Gap analysis is conducted to assess the alignment between Perum Peruri's CP and CPS with the principles of Business Practices Management Webtrust Certification Authorities. The results of the gap analysis indicate that no gaps are identified based on the checklist conducted by the author. This indicates that Perum Peruri's CP and CPS already comply with the principles set by Business Practices Management Webtrust Certification Authorities. This research significantly contributes to ensuring that Perum Peruri maintains compliance with international principles in the provision of electronic certification services. The findings of this study can serve as a reference for other electronic certification providers to improve and enhance the quality and security of their electronic certification management systems, particularly in the management of CP and CPS.